Evaluation of Sacrum Measurements in Healthy Individuals and Patients with L5-S1 Spondylolisthesis - Erbek, Esin; Dogan, Nadire Unver; Oztürk, Mehmet; Akdam, Neriman; Fazliogullari, Zeliha; Karabulut, Ahmet Kagan (European Journal of Therapeutics, 2024)
Objective: In recent studies, the relationship between sacrum morphology and orientation and spondylolisthesis has gained importance. The present study aimed to compare the morphometry of the sacrum between patients with L5-S1 spondylolisthesis and healthy subjects on multidetector computed tomography (MDCT) images. Methods: In this study, abdominopelvic MDCT images of 191 individuals (age range 20-92 years; 101 males and 90 females; 56 patients diagnosed with L5-S1 spondylolisthesis and 135 healthy individuals) were retrospectively evaluated. In this study, the sacrum parameters (Intercornual distance (ICD), sacral hiatus length (LHS), anteroposterior diameter of hiatus at the apex of sacral hiatus(APCWHSA), sacral height (SH), sacral table angle (STA), sacral table index (STI), S1 superior angle (S1A), sacral slope(SS)) evaluated morphometric and morphological in healthy individuals and patients with L5-S1 spondylolisthesis. Kolmogorov–Smirnov test was used to test the normality, which is one of the parametric test assumptions, of the data. Results: Age parameter was found statistically significant higher in the patient group (p<0.001). STA, S1A, SH, LHS and APCWHSA measurements were found to be significantly higher in the healthy group. (p<0.001, p<0.001, p=.008, p=.005, and p=.002, respectively). STI and ICD were found to be significantly higher in women in the healthy group (p=.031, p=.010), while SH parameter was found statistically significant higher in men in the healthy group (p=.007). SS was found statistically significant lower in the healthy group (p<0.001). S1A, L5-S1 spondylolisthesis was found statistically significant higher than Grade 1, Grade 2 according to the degree of slippage (p=.045). Conclusion: The results of this study showed that sacral morphology is important in the development or at least progression of spondylolisthesis.